(untitled) (Mongolian Journal of Applied Linguistics, 2024)
This article explores the concept of arγal, one of the main concepts in Mongolian culture and linguistics, from the perspective of spatial meaning. In addition to reflecting the culture of a particular time, words and phrases are also connected to spatial meaning. The geographical environment plays a significant role in shaping the development of word and phrase characteristics. As a cultural phenomenon, language is influenced by spatial factors. This is because language users are always situated within a specific geographic space, and the culture of that space affects their thoughts, consciousness, and so on. Consequently, the cultural understanding of a space shapes the vocabulary system, grammatical rules, phonetic patterns, and artistic representational techniques that are unique to that language. Furthermore, this article examines the formation of language and cultural systems within these spatial contexts. Монгол хэлний “аргал” хэмээх цогц ойлголтод хийсэн ажиглалт Хураангуй: Тус өгүүлэлд “Аргал” хэмээх цогц ойлголтыг соёл, хэл шинжлэлийн үндсэн ойлгогдохууны нэг болох орон зайн утга илтгэх талаас ажиглав. Үг хэл нь цаг хугацааны соёлыг илэрхийлээд зогсохгүй орон зайн утгаас ангид зүйл биш юм. Газар зүйн орчин тойрон нь үг хэлний онцлог буй болоход чухал нөлөө үзүүлдэг. Соёлын үзэгдэл болохын хувьд хэл нь орон зайнаас ангид зүйл биш юм. Учир нь хэлний үйл ажиллагаа эрхэлдэг субъект нь газар зүйн тодорхой орон зайн бүтцэд ямагт оршдог бөгөөд энэхүү орон зайн соёл нь хэлээр харилцагч ард түмний бодол санаа, ухамсар гэх мэтэд нөлөөлдөг байна. Тиймээс энэхүү орон зайн соёлын талаарх ойлголт нь тухайн хэлэнд өвөрмөц үгсийн сангийн систем, хэл зүйн дүрэм, дуудлагын хэв ёс, уран сайхнаар дүрслэх арга ухааныг бий болгодог. Улмаар газар зүй, орон зайн хүрээнд хэл, соёлын тогтолцоо бий болдог тухай энэ өгүүлэлд авч үзнэ. Түлхүүр үг: Аргал, цогц ойлголт, газар зүй, орон зай, зүйр цэцэн үг, хэл соёл